INTERVENSI PEMERINTAH PADA MEKANISME PASAR DALAM EKONOMI ISLAM - Purwanti, Eka (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2020)
Islam has regulated the role of government in the economic field, for example on price and market mechanisms. The government is the party that has the authority to form various regulations in the economic field. Islamic economic considers that the state, market, and individual are in balance, so that one can’t be more dominant. Government intervention can be carried out if the market is in unstable, well monopolies and boycotts. In the concept of Islamic economics, how to control prices can be determined from the cause.